Factors associated with maternal mortality at advanced maternal age: a population-based case – control study - McCall, S; Nair, M; Knight, M (Wiley, 2016)
Objective: This study aimed to examine the factors associated with maternal mortality among women aged ≥35 years. Design: Unmatched population based case–control study. Setting: United Kingdom. Population: Between 2009 and 2012, 105 cases of maternal deaths aged ≥35 years were extracted from the surveillance database of the MBRRACE-UK confidential enquiries into maternal deaths in the UK. In addition, 766 controls aged ≥35 years were identified from the UK Obstetric Surveillance System (2005–2012). Methods: Risk factors known to be associated with maternal mortality and morbidity and for which data were available were examined for their association with maternal mortality among women ≥35 years using logistic regression analysis. Main outcome measures: Odds ratios and 95% confidence intervals associated with maternal death. Results: Five factors were found to be significantly associated with increased odds of death among women aged ≥35 years: smoking during pregnancy (adjusted odds ratio (aOR) 2.06, 95% CI 1.13–3.75), inadequate use of antenatal care (aOR 23.62, 95% CI 8.79–63.45), medical co-morbidities (aOR 5.92, 95% CI 3.56–9.86) and previous pregnancy problems (aOR 2.06, 95% CI 1.23–3.45). The odds associated with death increased by 12% per year increase in age (aOR 1.12, 95% CI 1.02–1.22). Conclusion: Age was associated with maternal mortality even after adjusting for other known risk factors. Importantly, this study showed an association between maternal mortality and smoking among women aged 35 years or older. It emphasises the importance of public health action to reduce smoking levels and address trends in rising maternal age.